Conservação de aves no Brasil: revisão das mudanças ocorridas na última década - Frade, Mariana Santos (2019)
During the European Middle Age, the human being have distanced from nature due to the increased use of books for studies. However, with the growth of large cities and development of industry, the sense of belonging and the desire to return to nature began to emerge. Over the years, the concern with taking care of the natural environment was expanding until it reached the birds. Several institutions and programs have emerged to focus on taking care of this group. In 2005, the researchers Marini and Garcia, concerned about publicizing the conservation status of birds in the country, evaluated and presented an overview of bird conservation in Brazil, showing the main threats, plans and proposals for their conservation. In 2006, the same authors published the Comparative study of the global, national and state threatened bird list in Brazil, comparing the lists of cited species and number of threatened species by threat category. In view of that, after more than a decade, the objective of this study was develop a review of the changes that have occurred about bird conservation in Brazil. In order to do so, the number of new species described in the country, changes in conservation status of threatened species at national and global levels and conservation initiatives targeting these species were evaluated. The results obtained comprised 27 new bird species described for the country; with 221 species of threatened, extinct and extinct birds in the wild currently at national and global level. Changes to the national list were: 39 species had changes in their conservation status (26 species for a more critical level and 13 species for a lower level), 61 maintained the same status, 16 left the list of threatened species, 76 joined (one as regionally extinct) and three were extinguished. Changes to the global list were: 26 species had changes in their conservation status (12 species for a more critical level and 14 for a lower level), 86 maintained the same status, 16 left the threatened list and 60 joined. The similarity between the periods was 57% (Jaccard index = 0.57 and Sørensen index = 0.73), indicating that the 2006 and 2018 lists still contain many species in common but also many different ones. From 2008, 16 National Action Plans that contemplate the birds were created, benefiting a total of 245 species. Several conservation initiatives have been implemented. However, even if institutions and researchers fight for the conservation of endangered species, the tendency is for the number to increase even more because currently there are no prospects of public policies to combat deforestation, strengthening of environmental inspection and creation of protected areas in the country.